Toward a non-invasive diagnostic tool for Helicobacter pylori ‒ insights from ELISA-based biomarker profiling - Radhi, Hameed Majeed; Sahip, Mohsin Abbas; Abdalredha, Redha Dawud (Rzeszów University Press, 2026)
Introduction and aim. This study aimed to evaluate the diagnostic performance of a novel ELISA-based panel of virulence-associated antibodies (anti-CagA, anti-UreB, and anti-HpNAP IgG) for early detection of Helicobacter pylori infection. Material and methods. In this cross-sectional study of 40 dyspeptic patients, ELISA results were compared with histopathology and stool antigen testing as reference standards. Diagnostic accuracy was assessed using receiver operating characteristic (ROC) curve analysis, and predictors were evaluated through logistic regression. Results. Anti-CagA IgG achieved the highest diagnostic performance (AUC=0.95; sensitivity=90.9%; specificity=94.4%), followed by anti-UreB (AUC=0.92) and anti-HpNAP (AUC=0.89). The combined biomarker model reached an AUC of 0.97, demonstrating strong correlation with both infection status and symptom severity. Agreement between stool antigen testing and histopathology was high (κ=0.80). Conclusion. This study provides the first regional validation of a standardized three-marker ELISA panel that demonstrated high accuracy as a non-invasive diagnostic approach for early H. pylori detection, offering a cost-effective tool for use in resource-limited settings.
The study protocol was approved by the Institutional Review Board of Al-Hakim Teaching Hospital – Maysan (ethical approval no.: 24548, approval date: 15 October 2024).
Keywords: anti-CagA IgG; biomarker panel; ELISA; Helicobacter pylori; histopathology; non-invasive diagnosis